2019
DOI: 10.7759/cureus.5603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Premorbid Antiplatelet Medication Use on Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage: A Propensity Score-matched Study

Abstract: IntroductionDelayed cerebral ischemia (DCI) is a serious complication of aneurysmal subarachnoid hemorrhage (aSAH) and a major predictor of poor functional outcomes in patients surviving the initial insult. Several theories have postulated that platelet activation, microthrombi formation, and subsequent vasospasm are mechanisms involved. We, therefore, assessed the effect of premorbid antiplatelet medication (APM) use on discharge functional outcomes and cerebral infarction due to DCI in patients presenting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…66 On the other hand, a recent systematic review in which the majority of cases were treated by coil embolization also showed a significant reduction in poor outcome. 67,68 Although a recent retrospective study showed that double antiplatelet therapy might be effective, a large-scale RCT will be required to verify its significance. 69,70 As another treatment method for microthrombosis, there have been reports showing the effectiveness of ADAMTS13, which has an antiplatelet effect by inhibiting VWF-dependent platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…66 On the other hand, a recent systematic review in which the majority of cases were treated by coil embolization also showed a significant reduction in poor outcome. 67,68 Although a recent retrospective study showed that double antiplatelet therapy might be effective, a large-scale RCT will be required to verify its significance. 69,70 As another treatment method for microthrombosis, there have been reports showing the effectiveness of ADAMTS13, which has an antiplatelet effect by inhibiting VWF-dependent platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…DCI is the leading cause of disability in aSAH surviving the initial insult,19 and its exact pathogenesis is yet to be elucidated; inflammatory cascade activation and increased platelet aggregability have been implicated as potential underpinnings 20. Therefore, the role of AT in aSAH has been controversial, with conflicting results in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nimodipine and acelysin can be considered important elements of drug therapy of subarachnoid hemorrhage, necessary for the prevention of secondary complications of a cerebral aneurysm rupture. Despite some positive experience of using these drugs in the treatment of subarachnoid hemorrhages [10,11,12], their influence on the mechanisms of brain cellular damage, reactiveness and death still remains insufficiently studied.…”
mentioning
confidence: 99%